PERSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN TERHADAP PENGGUNAAN E-LEARNING - Dewi Sartika Pratiwi; Totoh Andayono (CIVED, 2019)
Abstack – This research is about Student Perception of Building Engineering Education  Study Program on the Use of E-learning. The background of this study is the results of the author's research with students of the Building Engineering Education Study Program in lectures using e-learning, it can be concluded that students have not used e-learning in the lecturing process. This study aims to determine student perceptions of the use of e-learning. The population of this research is the students of Building Engineering Education Study Program who use e-learning in the lecture process in the January-June 2019 semester, amounting to 137 students and a sample of 55 students. The research data was collected through a questionnaire given to students who were selected as research samples to know student’s perceptions of the use of e-learning. Based on the results of the research carried out it can be concluded that the results of the study show that perceptions of students of the Building Engineering Education Study Program on the use of e-learning amounted to 72.26%, the category is quite good, it can be concluded that students who use e-learning have a fairly good perception in the lecture process. Keywords: Perception, E-learning